2018
DOI: 10.1002/jcb.27199
|View full text |Cite
|
Sign up to set email alerts
|

ERβ targets ZAK and attenuates cellular hypertrophy via SUMO‐1 modification in H9c2 cells

Abstract: Aberrant expression of leucine zipper- and sterile ɑ motif-containing kinase (ZAK) observed in pathological human myocardial tissue is associated with the progression and elevation of hypertrophy. Our previous reports have correlated high levels of estrogen (E2) and abundant estrogen receptor (ER) α with a low incidence of pathological cardiac-hypertrophy and heart failure in the premenopause female population. However, the effect of elevated ERβ expression is not well known yet. Therefore, in this study, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…No study has specifically addressed the regulation of ZAK by the UPS. However, it has been reported that ZAK protein abundance can be modulated by treatment with high concentrations of doxorubicin or by expression of estrogen receptor b in a proteasome-independent manner (Sauter et al, 2010;Pai et al, 2018). In these studies, pharmacological inhibition of the proteasome with MG132 showed no effect on ZAK protein levels.…”
Section: B the P38 And C-jun N-terminal Kinase Signaling Pathwaysmentioning
confidence: 87%
“…No study has specifically addressed the regulation of ZAK by the UPS. However, it has been reported that ZAK protein abundance can be modulated by treatment with high concentrations of doxorubicin or by expression of estrogen receptor b in a proteasome-independent manner (Sauter et al, 2010;Pai et al, 2018). In these studies, pharmacological inhibition of the proteasome with MG132 showed no effect on ZAK protein levels.…”
Section: B the P38 And C-jun N-terminal Kinase Signaling Pathwaysmentioning
confidence: 87%
“…In addition, it has been proven that the PI3K/Akt signalling pathway is activated in response to the chronic upregulation of oestrogen receptor β [42]. Furthermore, Notch1 has been demonstrated to modulate the PI3K/Akt axis by regulating PTEN expression in various tissues [43]. These observations prompted us to investigate the relationship between Notch1, PI3K/Akt signalling and oestrogen receptor β activation in damaged cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
“…SUMO1 was also found to improve the oxidative stress response during increased cardiac hypertrophy [ 37 ]. SUMO1 transfection with adenovirus after TAC, a model of heart failure induced by stress overload, prevented the occurrence of cardiac hypertrophy, blocked the negative effect of hydrogen peroxide on SERCA2a, and decreased the oxidative stress index in mice [ 38 ].…”
Section: Sumo Machinery and Cvdmentioning
confidence: 99%